2016
DOI: 10.1038/nplants.2016.25
|View full text |Cite
|
Sign up to set email alerts
|

Local auxin metabolism regulates environment-induced hypocotyl elongation

Abstract: A hallmark of plants is their adaptability of size and form in response to widely fluctuating environments. The metabolism and redistribution of the phytohormone auxin play pivotal roles in establishing active auxin gradients and resulting cellular differentiation. In Arabidopsis thaliana, cotyledons and leaves synthesize indole-3-acetic acid (IAA) from tryptophan through indole-3-pyruvic acid (3-IPA) in response to vegetational shade. This newly synthesized auxin moves to the hypocotyl where it induces elonga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
125
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(136 citation statements)
references
References 50 publications
10
125
0
1
Order By: Relevance
“…The expression of members of the SAUR19 subfamily of early auxin-responsive genes (Chapman et al, 2012;Spartz et al, 2012) is very rapidly shade induced in hypocotyls, and SAUR22 induction still occurs in the pin3 pin4 pin7 and yuc2 yuc5 yuc8 yuc9 mutants, suggesting the involvement of a local response ( Figure 4). The rapid induction of SAUR22 could be due to locally regulated auxin homeostasis (Zheng et al, 2016). Consistent with such a possibility, we found that DII-VENUS levels declined in the hypocotyls of shade-treated pin3 pin4 pin7 seedlings (Supplemental Figure 4H).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The expression of members of the SAUR19 subfamily of early auxin-responsive genes (Chapman et al, 2012;Spartz et al, 2012) is very rapidly shade induced in hypocotyls, and SAUR22 induction still occurs in the pin3 pin4 pin7 and yuc2 yuc5 yuc8 yuc9 mutants, suggesting the involvement of a local response ( Figure 4). The rapid induction of SAUR22 could be due to locally regulated auxin homeostasis (Zheng et al, 2016). Consistent with such a possibility, we found that DII-VENUS levels declined in the hypocotyls of shade-treated pin3 pin4 pin7 seedlings (Supplemental Figure 4H).…”
Section: Discussionsupporting
confidence: 80%
“…Although shade-induced hypocotyl elongation requires an interaction between cotyledons and hypocotyls (see above), some shade responses occur in an organ-autonomous manner (Morgan et al, 1980;Procko et al, 2014;Nito et al, 2015;Zheng et al, 2016). The expression of members of the SAUR19 subfamily of early auxin-responsive genes (Chapman et al, 2012;Spartz et al, 2012) is very rapidly shade induced in hypocotyls, and SAUR22 induction still occurs in the pin3 pin4 pin7 and yuc2 yuc5 yuc8 yuc9 mutants, suggesting the involvement of a local response ( Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…As described for the AtGH3.5 gain-of-function mutants and overexpression of other IAA-conjugating GH3 proteins in Arabidopsis and rice (16,17,20,(29)(30)(31), AtGH3.5 overexpression decreased IAA and increased IAA-Asp levels (Fig. 4 A and B).…”
Section: Atgh35mentioning
confidence: 60%
“…Investigations of the biological action of GH3 proteins from a variety of plants have focused largely on JA and IAA; however, biochemical and structural studies suggest that the functional diversity of the GH3 protein family may be wider than previously understood. Of the 19 GH3 proteins in A. thaliana, one is required for JA-Ile biosynthesis, six are associated with conjugation and inactivation of IAA, and the rest either lack a physiological substrate or remain to be characterized (3,7,(15)(16)(17)(18)(19)(20). Of these proteins, AtGH3.5 was proposed to have a dual role in IAA and SA homeostasis (16,17).…”
Section: Atgh35mentioning
confidence: 99%
See 1 more Smart Citation